The “sandwich” procedure for paracentral rheumatoid corneal perforation: a case report with 6-year follow-up and literature review - Zhang, Yi; Liu, Hanjing; Li, Qing; Zhu, Yan; Zhu, Yu-guang (Frontiers in Medicine, 2025)
Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease often associated with ocular manifestations. In rare cases of RA, paracentral rheumatoid corneal perforation may occur. We report the case of a 53-year-old monocular woman with a 20-year history of RA who presented to the clinic with a paracentral corneal perforation. Slit-lamp examination revealed a 2-mm diameter paracentral perforation with an iris plug. The patient was clinically diagnosed with sterile rheumatoid corneal perforation. We describe an innovative “sandwich” procedure developed for addressing the corneal perforation. Initially, a partial thickness limbal groove was created outside the perforation, followed by the formation of a semicircular intrastromal pocket extending approximately 2 mm inside the perforation edge. A lamellar graft was then fashioned and inserted into the intrastromal pocket. Subsequently, the limbal groove was closed, and a conjunctival flap was used to cover the perforated area. Upon follow-up, the “sandwich” procedure provided sufficient tectonic support for the patient’s only eye, resulting in a stable ocular surface. Over a 6-year follow-up period, the postoperative best-corrected visual acuity (BCVA) was maintained at 20/50. To the best of our knowledge, this is the first report of the “sandwich” procedure for paracentral rheumatoid corneal perforation.